Studies of spin-orbit coupling phenomena in magnetic semiconductors - Howells, Bryn (2015)
Hard disk drives (HDDs) have been the dominant secondary memory device in computing for over 50 years, while more recently magnetoresistive random access memory (MRAM) has emerged as a candidate for primary computing memory. Both HDDs and MRAM store information in the polarity of a magnetic layer, which is written and read by non relativistic mechanisms. There is now gathering interesting in using relativistic mechanisms whose origins lie with spin-orbit coupling (SOC) for MRAM writing because of potential benefits in terms of scalability, device design, and efficiency. This thesis investigates the fundamental physics of SOC phenomena that can write (spin-orbit torque (SOT), Neel order SOT) or read (anisotropic magnetoresistance (AMR), magnetic gating) the magnetic state by the application of electrical current. These phenomena are studied in ferromagnetic and antiferromagnetic semiconducting materials that offer a relevant electrical conductivity for integration into commercial electronic devices.